Método para cálculo global de eficiência em sistemas de ar comprimido: aplicação a três estudos de caso - Rischter, Douglas (My University, 2019)
The consumption of electricity is increasing in proportions that the generation does not follow, so when energy efficiency actions are carried out, they generate more positive impacts on society. Thinking about this energy consumption reduction bias, the present work developed a method to evaluate the overall efficiency in compressed air systems. Such a method takes into account the air leakage rate in the compressed air network, the pressure drop in the pipe that the air flows and the compressed air pressure provided by the generating system. Therefore, the developed method was implemented in three different installations, each with a different equipment configuration. The application of the method in the first installation showed a potential reduction of 39.2% energy consumption in the compressed air system, but after performing the suggested actions, the real gain was 27.9%. The application of the method in the second installation projected a reduction in energy consumption of 49.5% in the compressed air system, and after the implementation of the actions, the real gain was 11.9%. The application of the method in the third installation showed an energy reduction potential of 51.0%, but after the implementation of the actions, the real gain founded was 9.5%. The major impact factor that caused the difference between the projected gain and the actual gain in the three facilities was the failure of the companies in fully implement the actions suggested. The results were satisfactory, showing the feasibility of applying this method to calculate the overall efficiency in compressed air systems.
O consumo de energia elétrica vem aumentado em proporções que a geração não acompanha, portanto, quando ações de eficiência energética são realizadas, estas geram mais impactos positivos para a sociedade. Pensando neste viés de redução de consumo de energia, o presente trabalho desenvolveu um método para avaliar a eficiência global em sistemas de ar comprimido. Tal método leva em conta o índice de vazamentos de ar na rede de ar comprimido, perda de carga na canalização na qual o ar escoa e a pressão de ar comprimido fornecida pelo sistema de geração. Para tanto, o método desenvolvido foi implementado em três instalações distintas, cada uma com uma configuração diferente de equipamentos. A aplicação do método na primeira instalação mostrou um potencial de redução de consumo de 39,2% de energia no sistema de ar comprimido, porém após a realização das ações sugeridas, o ganho real foi de 27,9%. A aplicação do método na segunda instalação projetou uma redução no consumo energético de 49,5% no sistema de ar comprimido, e após a implementação das ações o ganho real foi de 11,9%. A aplicação do método na terceira instalação mostrou um potencial de redução energética na ordem de 51,0%, porém após a implementação das ações, o ganho real foi de 9,5%. O fator de maior impacto que ocasionou a diferença entre o ganho projetado para o ganho real nas três instalações foi à não execução das ações sugeridas na sua totalidade por parte das empresas. Os resultados encontrados foram satisfatórios, mostrando a viabilidade da aplicação deste método para calcular a eficiência global em sistemas de ar comprimido.
Keywords: Energia elétrica - Consumo; Ar comprimido; Motores elétricos; Electric power consumption; Compressed air; Electric motors